The evolution and development of left/right asymmetry in the Lophotrochozoa - Kenny, NJ (2014)
Left/right (L/R) asymmetries, differences in morphology between the otherwise mirrored left- and right-hand sides of the body, are found in animals across the Bilateria. For many years it was thought that the mechanisms for establishment of these asymmetries had evolved separately in the three superphyla that constitute the Bilateria, but the discovery in 2009 that the TGF-beta ligand Nodal shares a conserved role in the Deuterostomia and Lophotrochozoa has re-ignited debate and interest in this field. In this thesis, work examining the establishment and maintenance of L/R asymmetries in the lophotrochozoan superphylum is presented, aimed at uncovering the wider conservation of these pathways across the Bilateria. Illumina sequencing and a range of de novo assembly techniques were used to derive genomic and transcriptomic data respectively for two primary model organisms, the limpet Patella vulgata and the serpulid annelid Pomatoceros lamarckii. Additionally, collaborative work lead to the derivation of transcriptomes for two other mollusc species and the genome of the monogont rotifer Brachionus plicatilis. A range of analysis was performed on these novel resources and is detailed here, with particular reference to the transcription factor cassettes contained in these datasets. These sequence resources formed the basis for examination of the breaking of initial symmetry in these model organisms. Known read-outs of correct establishment of L/R asymmetry, the expression of genes Nodal and Pitx on the right of the body, were codified in the course of normal development in P. vulgata. Pharmacological inhibitors of genes implicated in the establishment of L/R asymmetry, particularly ATPase ion channels, were then applied to embryos. After development, markers of normal development were assayed for signs of bilateral inversion. Although radialised phenotypes were observed, it is unclear whether these are specifically the result of L/R asymmetry defects. The localisation of ATPase mRNA and serotonin, often posited as a small molecule potential morphogen, were also assayed, although no conclusions could be drawn as to a role in the establishment of L/R asymmetry for these molecules, counter to some evidence from vertebrates. Once symmetry is broken, the TGF-beta pathway is responsible for the communication, specification and maintenance of tissue identity across the L/R axis. The novel sequence resources described in this thesis provided a comprehensive window into this signalling cassette, and detailed here is a treatment of the TGF-beta pathway within the Lophotrochozoa. Ligand diversity has increased markedly in some clades, while signal transduction and regulatory steps are relatively unchanged. This work has increased our knowledge of lophotrochozoan biology and particularly the mechanisms underpinning the establishment of asymmetry in this under-researched clade, however, much remains to be discovered about the ultimate origin of asymmetry itself.